High mortality within 90 days of diagnosis in patients with Cushing's syndrome: results from the ERCUSYN registry. Issue 5 (November 2019) - Valassi, Elena; Tabarin, Antoine; Brue, Thierry; Feelders, Richard A; Reincke, Martin; Netea-Maier, Romana; Tóth, Miklós; Zacharieva, Sabina; Webb, Susan M; Tsagarakis, Stylianos; Chanson, Philippe; Pfeiffer, Marija; et al.
Abstract : Objective: Patients with Cushing's syndrome (CS) have increased mortality. The aim of this study was to evaluate the causes and time of death in a large cohort of patients with CS and to establish factors associated with increased mortality. Methods: In this cohort study, we analyzed 1564 patients included in the European Registry on CS (ERCUSYN); 1045 (67%) had pituitary-dependent CS, 385 (25%) adrenal-dependent CS, 89 (5%) had an ectopic source and 45 (3%) other causes. The median (IQR) overall follow-up time in ERCUSYN was 2.7 (1.2–5.5) years. Results: Forty-nine patients had died at the time of the analysis; 23 (47%) with pituitary-dependent CS, 6 (12%) with adrenal-dependent CS, 18 (37%) with ectopic CS and two (4%) with CS due to other causes. Of 42 patients whose cause of death was known, 15 (36%) died due to progression of the underlying disease, 13 (31%) due to infections, 7 (17%) due to cardiovascular or cerebrovascular disease and 2 due to pulmonary embolism. The commonest cause of death in patients with pituitary-dependent CS and adrenal-dependent CS were infectious diseases ( n = 8) and progression of the underlying tumor ( n = 10) in patients with ectopic CS. Patients who had died were older and more often males, and had more frequently muscle weakness, diabetes mellitus and ectopic CS, compared to survivors. Of 49 deceased patients, 22 (45%) died within 90 days from start of treatment and 5 (10%) before any treatment was given. The commonest cause of deaths in these 27 patients were infections ( n = 10; 37%). In a regression analysis, age, ectopic CS and active disease were independently associated with overall death before and within 90 days from the start of treatment. Conclusion: Mortality rate was highest in patients with ectopic CS. Infectious diseases were the commonest cause of death soon after diagnosis, emphasizing the need for careful clinical vigilance at that time, especially in patients presenting with concomitant diabetes mellitus.